DESAIN DAN EVALUASI KINERJA MESIN PENCACAH NILAM - Andriani Lubis; Tineke Mandang; Wawan Hermawan; Sutrisno Mardjan (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2021)
Design and Performance Evaluation of Patchouli Chopping Machine. Aceh is one of the largest patchouli producing regions in Indonesia with an average contribution of patchouli production for the last 6 years of 415 tons/year. Patchouli oil is one of Indonesia's mainstay commodities compared to other essential oils. The demand of essential oils for raw materials of cosmetics, perfumes and pharmaceutical products industries continues to increase. The research objective was to design a patchouli chopper machine with the right type of cutting knife. This research was conducted using engineering methods including: problem identification, formulation of patchouli chopper machine design, prototyping, functional testing, and performance testing. The prototype of this chopper machine used an electric motor as its driving force. The machine was divided into 4 major parts, namely hopper, chopper cylinder, chopper knife and outer. The transmission section used a belt and pulley. The patchouli chopper machine used two types of cutting knife which were the circular knife and the double blade to produce a chopping size of 7-10 cm. The results of the performance test and giving weight scaled values on the patchouli chopper machine showed that double blade performa was better compared to the circular knife type to use because it had the highest score of 3.375 and could be combined in the patchouli harvester. This performance can be seen from the actual engine capacity of 255.74 kg/h, the power needed to chop patchouli stem of 528.55 W with the energy requirement of 7.44 kj/kg, percentage of chopped length of 95.5 % and the efficiency of the electric motor was 98.1% at a blade rotational speed of 745 rpm. Keywords: patchouli oil, chopping, cutting knife, machine capacity ABSTRAK Aceh merupakan salah satu daerah penghasil nilam terbesar di Indonesia dengan kontribusi produksi nilamnya selama 6 tahun terakhir rata-rata mencapai 415 ton/tahun. Minyak nilam merupakan salah satu komoditas andalan Indonesia dibandingkan minyak atsiri lainnya. Kebutuhan minyak atsiri untuk bahan baku industri produk kosmetik, parfum dan farmasi terus meningkat. Tujuan penelitian adalah merancang mesin pencacah batang nilam dengan tipe pisau pemotong yang tepat. Penelitian dilakukan menggunakan metode rekayasa meliputi: identifikasi masalah, perumusan desain mesin pencacah nilam, pembuatan prototipe, uji fungsional, dan uji kinerja. Prototipe mesin pencacah menggunakan tenaga motor listrik sebagai penggeraknya terbagi menjadi 4 bagian yaitu hopper, silinder pencacah, pisau pencacah dan outer. Pada bagian transmisi menggunakan sabuk dan puli. Mesin pencacah nilam dibedakan menjadi dua jenis berdasarkan tipe pisau pemotong yaitu tipe circular knife dan tipe double blade untuk menghasilkan cacahan batang nilam dengan panjang ukuran cacahan 7-10 cm. Hasil uji kinerja dan penggunaan nilai bobot berskala pada mesin pencacah nilam menunjukkan bahwa penggunaan pisau pencacah tipe double blade merupakan pisau terbaik dibandingkan dengan tipe circular knife karena memiliki skor tertinggi 3,375 dan dapat digabungkan pada mesin pemanen nilam nantinya. Kinerjanya dapat dilihat dari kapasitas aktual mesin 255,74 kg/jam, daya terbesar yang dibutuhkan untuk mencacah batang nilam 528,55 W dengan kebutuhan energi pencacahan 7,44 kj/kg, persentase panjang hasil pencacahan 95,5% dan efisiensi motor listrik 98,1% pada kecepatan putar poros pisau 745 rpm.Kata kunci: batang nilam, pencacahan, pisau pemotong, kapasitas mesin